Factors associated with work related injuries among workers of an industry in Malaysia - Nkemakolam, Obi Adaeze; Ariffin, Ahmad Azuhairi; Zainuddin, Huda (Community Health Society Malaysia, 2017)
Background: Industrial accidents are very common till date; there are thousands of workers getting injured every day. Work related injury in the workplace is a global major risk factor to the worker's health, which results into serious health, social, and economic consequences on workers and their employers. The objective of the study was to determine the organizational, occupational and behavioural risk factors associated with work related injuries among workers of an industry. Materials and Methods: This is a cross sectional study involving 215 workers of an industry in Malaysia. The required sample size was calculated using the two proportions formula. Result: The overall prevalence of work related injuries was 73.5% (82.1% among male and 66.7% among female). The variables found to be significantly associated with work related injuries were: ethnicity, educational background, unit of operation, limited work space, noise, job task demand and administrative control (p<0.005). Occupational factor such as the type of machine (electrical motor) used (Fisher’s exact = 8.88, p= 0.031) and behavioural factor such as job task demand (felling tired and dizzy) (mean=2.80±0.76 vs. mean=2.18±0.60; t-test=6.24, p<0.001) reported high prevalence of work related injuries (p value = 0.001). Conclusion: The prevalence of work related injuries in this study was high. Despite this high prevalence, the consideration of the effectiveness of relevant guidelines and policies for preventive action should be put in place and training courses on the proper usage of machines can reduce the number of work related injuries in Malaysia.